A Methodology for Daylighting Optimisation in Academic Libraries: Case Study of EMU Main Library - Mohamedali, Ahmed (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Nowadays, most of the buildings are designed without considering the sustainability or responding to natural conditions which becomes a noticeable international trend. It is commonly preferable to design building in response to natural light and site potentials as views. This has impacts on the several dimensions as passive solar heating, reduction in electrical consumption and affecting the human health and psychology. As future architects and researchers, it's imperative for us to adapt sustainability measures in architectural design as daylighting to enhance the space quality needed but tactlessly the occurrence of daylighting is not always optimistic as it is anticipated. This research work aims to maximize benefits of daylighting measures of the EMU main library, through optimizing daylight usage by adopting shading strategies and reducing glare negative effects, to create appropriate visual efficiency for various tasks to be performed in the building. A well laid-out and logical methodologies will provide a great backbone of the research, and would allow to build some reliable results. Thus, this research is combining ‘Problem Solving’, ‘Case Study’ and ‘Surveying’ methodologies to obtain some concrete solutions. Firstly, qualitative methodology was used to identify the problem through observation and supported by questionnaire with real library building users. Then, quantitative methodology was adapted by using computer simulations to detect the problem statistically to find sustainable solution for the problems. Daylight is highly recommended to be used, but it is not appropriately being controlled for user to perform their visual tasks and replaced by the artificial lights that highly increase the energy consumption for EMU Main Library to achieve visual comfort, and the required levels of satisfaction. Certain strategies are recommended to be introduced in a way to control excessive daylight and glare effects, throughout daytime and between seasons, to achieve near optimum visual comfort in libraries indoor space. Based on annual analysis results, the study is evaluation criteria rest on universal standards combination and modifications to find proper assessment method for space visual performance. Keywords: Sustainability, Visual Comfort Metrics, Glare, User’s Performance, Daylight Strategies, Daylight Control.

ÖZ: Günümüzdeki binaların çoğu, sürdürebilirliği dikkate almaksızın veya dikkat çekici bir uluslararası trend haline gelen doğal koşullara tepki vermeksizin, tasarlanmıştır. Genel olarak, binaların tasarım şekli, doğal ışığa ve arazinin potansiyellerine yanıt verebilmesi için tercih edilir. Bu, pasif güneş ısıtması, elektrik tüketimindeki azalma ve insan sağlık ve psikolojisini etkileyen çeşitli boyutları kapsamaktadır. Geleceğin mimarları ve araştırmacıları olarak, mimari tasarımdaki sürdürebilirlik tedbirlerini, ihtiyaç duyulan alan kalitesini artıracak şekilde, gün ışığı olarak adapte etmek zorunludur, ancak gün ışığının oluşumu beklendiği kadar her zaman iyimser değildir. Araştırma çalışması, DAÜ ana kütüphanesinin, gün ışığının faydalarından, gölgelendirmeyi benimseyerek ve gün ışığı kullanımını optimize ederek, binada gerçekleştirilecek çeşitli görevler için parlamanın olumsuz etkilerini azaltmak ve uygun görsel verimlilik oluşturmak için maksimize stratejileri bulmayı amaçlar iyi düzenlenmiş ve mantıklı bir metodoloji, araştırmaya büyük bir destek sağlayacak ve güvenilir sonuçlar üretmesine izin verecektir. Bu nedenle, bu araştırma bazı somut çözümler elde etmek için ‘Problem Çözme’, ‘Örneklem Çalışması’ ve ‘Anket’ yöntemlerini birleştirmektedir. Öncelikle, sorunun gözlem yoluyla belirlenmesi için nicel metodoloji kullanılmış ve gerçek kütüphane kullanıcısı anketi ile desteklenmiştir. Ardından, nicel yöntem, problemi istatistiksel olarak tespit edebilmesi için bilgisayar simülasyonları kullanılarak uyarlanmış, problemlere sürdürülebilir çözüm bulunması amaçlanmıştır. Gün ışığının kullanılması tavsiye edilmektedir, fakat kullanıcıların görsel işlerini yerine getirebilmesini sağlayacak kadar, kontrol edilmemekte ve yerine görsel konfor ve gerekli tatmin seviyelerini sağlamak için DAÜ ana kütüphanesinin enerji tüketimini artıran yapay ışıklar kullanılmaktadır. Belli stratejilerin, kütüphanelerin kapalı mekanlarında en uygun görsel konfora erişmek için gündüzler ve mevsimler arasındaki aşırı gün ışığı ve parlama etkilerini kontrol altına alacak şekilde açıklanması önerilir. Anahtar Kelimeler: Sürdürebilirlik, Görsel Konfor Ölçütleri, Parlama, Kullanıcı Performansı, Gün Işığı Stratejileri, Gün Işığı Kontrolü.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2017. Supervisor: Assist. Prof. Dr. Harun Sevinç.
Keywords: Architecture; Light in Architecture; Interior lighting-Libraries; Interior lighting-Academic Libraries-Eastern Mediterranean University-Özay Oral Library; Sustainability; Visual Comfort Metrics; Glare; User’s Performance; Daylight Strategies; Daylight Control